Selected aspects of reclamation of soda waste landfill sites - Świdwa-Urbańska, Joanna; Urbański, Krzysztof (My University, 2012)
This paper presents leading trends and methods for the reclamation of soda industry waste landfill sites. The artide constitutes a synthetic study of the literature regarding the problems of land management of soda waste sedimentation tanks.

W artykule przedstawiono wiodące trendy w rekultywacji składowisk odpadów przemysłu sodowego i metody jej prowadzenia. Artykuł stanowi syntetyczne studium literatury dotyczącej problematyki zagospodarowania terenu osadników odpadów posodowych.
Wybrane aspekty rekultywacji składowisk odpadów posodowych
Geomatics and Environmental Engineering
Keywords: reclamation; rekultywacja; soda waste; odpady posodowe